2013
DOI: 10.4236/jacen.2013.24014
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial compounds from Rutaceae with activities against Flavobacterium columnare and Streptococcus iniae

Abstract: From the ethyl acetate extract of Murraya koenegii (Rutaceae) leaves, isomahanine (1) and mahanine (2) were isolated that showed antibacterial activity towards Flavobacterium columnare and Streptococcus iniae which caused columnaris disease and streptococcosis respectively. Isomahanine was found to have the strongest activity against F. columnare (isolate ALM-00-173) and S. iniae (isolate LA94-426) based on 24-h 50% inhibition concentration (IC 50) and minimum inhibition concentration (MIC). Although compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…(S.K. Raghav, 2006) (Ratheesh, M; Shyni, G L; Sindhu, G; Helen, A, 2010) Dada a diversidade de constituintes ativos e propriedades terapêuticas que lhe são atribuídas, a Arruda é inequivocamente uma planta com enorme potencial terapêutico também no tratamento de doenças oncológicas, cardiovasculares, e no tratamento de doenças infeciosas (Jafar, 2008); (Kumudini M. Meepagala, 2013) (Ivanovaa, Mikhovaa, Najdenskib, Tsvetkovab, & Kostovaa, 2005) (Freyner, et al, 2014) (Loonat & Amabeoku, 2014 (Hale, Meepagala, Oliva, Aliotta, & Duke, 2004).…”
Section: Discussão Dos Resultadosunclassified
“…(S.K. Raghav, 2006) (Ratheesh, M; Shyni, G L; Sindhu, G; Helen, A, 2010) Dada a diversidade de constituintes ativos e propriedades terapêuticas que lhe são atribuídas, a Arruda é inequivocamente uma planta com enorme potencial terapêutico também no tratamento de doenças oncológicas, cardiovasculares, e no tratamento de doenças infeciosas (Jafar, 2008); (Kumudini M. Meepagala, 2013) (Ivanovaa, Mikhovaa, Najdenskib, Tsvetkovab, & Kostovaa, 2005) (Freyner, et al, 2014) (Loonat & Amabeoku, 2014 (Hale, Meepagala, Oliva, Aliotta, & Duke, 2004).…”
Section: Discussão Dos Resultadosunclassified
“…Against fish pathogens, Wei et al (2008) showed that ethanol or methanol extract of M. koenegii leaves has antibacterial activity against A. hydrophila and other fish bacteria. In vitro experiments have shown that two compounds isolated from its ethyl acetate extract, namely isomahanine and mahanine, have antibacterial activity on Flavobacterium columnare and Streptococcus iniae, both major pathogens for tilapia culture (Meepagala, Schrader, and Burandt 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the search for effective and environmentally friendly mosquito control agents, we have examined natural sources such as microbes and plants and the synthetic analogs of natural products (Meepagala et al 2013, 2015, 2016, 2018). These plants and microbes have evolved in their ecological niches to produce defensive compounds against other competing organisms in their surroundings such as microbes, plants, and insects to enhance their survival.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we successfully isolated bioactive constituents from natural sources. We subsequently carried out synthetic modifications and total synthesis of marginally active natural compounds to achieve significantly higher insecticidal activity (Meepagala et al 2010, 2013). We have focused on the Rutaceae family as other members of this family are known to possess a range of bioactive compounds with algicidal, antifungal, insecticidal, and fungicidal activities (Meepagala et al 2005, 2019, 2013, Okagu et al 2021, Ombito et al 2021, Alam et al 2022).…”
Section: Introductionmentioning
confidence: 99%